Surgery for hypertrophic obstructive cardiomyopathy (HOCM): what to do with concomitant mitral insufficiency? - Messmer, Bruno J. (Journal of Thoracic Disease, 2017)
Mitral insufficiency is frequently associated with HOCM and generally results from systolic anterior motion (SAM) of the septal leaflet hindering early closure and correct coaptation of the valve.